Analysis of the Relationship Between the Percentage of Load Imbalance and Power Losses in Distribution Transformers at PT. PLN (Persero) ULP Binjai Timur - Alexius Victor Purba; Haris Gunawan; Dino Erivianto (SEAN Institute, 2026)
Distribution transformer is one of the most important components in the electric power distribution system. Distribution transformers often experience load imbalance problems. One previous study showed that load imbalance can reach 25.6% which contributes to increased power losses. This study aims to analyze the relationship between the percentage of load imbalance and the power losses incurred at PT. PLN (Persero) ULP East Binjai. This study was conducted with a quantitative approach by calculating the percentage of load imbalance and the resulting power losses. Data were collected through direct observation, voltage and current measurements, then calculations and analysis were carried out. The results showed that a greater percentage of load imbalance occurred at night at 12.96% while during the day at 10.03%. And the resulting power losses occurred at night at 853.3 Watts while during the day at 4,386.3 Watts. Thus, it can be concluded that the greater the percentage of load imbalance, the greater the power losses incurred.